Thermal growing season trends in east China, with emphasis on urbanization effects. (11th September 2012) - Yang, Xuchao; Tian, Zhan; Chen, Baode
Abstract Dense meteorological station network‐derived data on daily surface air temperatures over the period 1961–2007 were used to investigate the changes in the thermal growing season (GS) indicators for east China. The 394 stations are classified into six categories: metropolises, large cities, medium‐sized cities, small cities, suburbs, and rural area using satellite‐measured night‐time light imagery and census data. Only the temperature data on 258 small cities and rural stations were used to calculate the GS indicators to reflect more 'natural' changes in thermal GS parameters. During the studied period, the regional mean length of the GS significantly extended by 3.05 and 2.61 d decade−1 for base temperatures of 5 and 10 °C, respectively. This extension is attributed primarily to the GS initiating at an earlier time (2.49 and 2.10 d decade−1 for base temperatures of 5 and 10 °C, respectively), rather than to the delayed end of the GS (0.55 and 0.51 d decade−1 for base temperatures of 5 and 10 °C, respectively). The mean growing degree days (GDD) has increased by 51.84 and 35.89 degree days decade−1 on average at temperatures higher than 5 and 10 °C. When the temperature data from all the 394 stations(including metropolis, large city, medium city, and suburban) were used to calculate the GS indicators, urban heat island (UHI) effects were evident, especially in highly urbanized Yangtze River Delta. The GS extension and GDD increase in metropolises increased by more than onefold over those observed for rural areas. This result indicates significant UHI effects on climatic GS changes. On the basis of the GDD changes, we find that UHI effects contributed to more than 10% in the GDD increase at temperatures higher than 10 °C. Therefore, excluding the urbanization effects from station observational data in evaluating changes in GS indices is necessary, especially for regions characterized by rapid urbanization.